PERBANDINGAN KECEMASAN KEMATIAN BERDASARKAN TINGKAT PENDIDIKAN PADA KOMUNITAS HOMOSEKSUAL DI SAUMLAKI KEPULAUAN TANIMBAR - Ferdinan Sihombing; Rosalia; Susanti Niman (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2022)
The situation of being transgender and being a homosexual can make them feel like an alien. Homosexual behavior is very risky for the incidence of sexually transmitted diseases and the threat of death. The existence of this awareness of death raises a different response in each person, including anxiety. Not infrequently death anxiety is felt excessively and causes observable symptoms. This study aims to determine differences in death anxiety among homosexual groups in the Perwasi community in Saumlaki, Tanimbar Islands with various educational backgrounds, namely elementary, junior high, and high school/vocational schools. The research method used is comparative descriptive. Sampling used purposive sampling in which only willing homosexuals became research respondents. Death anxiety was measured using Templer's Death Anxiety Scale questionnaire containing 15 questions. It was found that all groups were at a low level of anxiety with a mean value of elementary education 4.46 (+1.330), junior high school education 4.79 (+0.893), and high school/vocational school education 4.83 (+1.466). One-way ANOVA showed no significant difference in anxiety levels between all groups. In conclusion, this study indicated that the three groups of respondents experienced low death anxiety and there was no significant difference in the mean score of death anxiety for all groups based on educational background.